PENGARUH JENIS MEDIA TERHADAP PERTUMBUHAN Nannochloropsis sp. - Eni Juniantari, Ni Kadek; Dewi Anggreni, Anak Agung Made; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
The aims of this study were to 1) determine the effect of media on the growth of Nannochloropsis sp., 2) find out the best type of growth media of Nannochloropsis sp. This study used a descriptive quantitative method. The medium used in this study consist of 3 types: Agricultural, Allen-Miquel, and Guillard medium. Observation of cell biomass concentration Nannochloropsis sp. was used haemacytometer with three replications. The results showed that each culture medium had a different optimum harvest time. Agriculture media, Allen-Miquel, and Guillard had the optimum harvest time which was 8, 12, and 11 days cultivation resvectively. The results observation of cell biomass concentration of Nannochloropsis sp. showed that the type of media had highly significant on growth of Nannochloropsis sp. Guiilard media was a medium that produced highest biomass cell Nannochloropsis sp. of 1.4 x 10 7 ± 2.0 cells/ml at 11 days cultivation. Keywords: Nannochloropsis sp., Media Type, Biomassa
Keywords: 37,